The Impact of Personality Traits and Knowledge on Entrepreneur Performance - Wan Farha, Wan Zulkiffli (2009)
It is widely accepted that entrepreneurship represents a real engine of economic development. The government acknowledge that to become success in the future not enough just have a good personality traits and intellectual, it more but it more depends on human capital. This study tends to exploit the model of personality traits and knowledge approach in order to capture the entrepreneurs' performance among entrepreneurs in Kota Bharu, Kelantan. Model of personality traits suggests four dimensions that determine traits which are need for achievement, locus of control, risk-taking propensity and tolerance for ambiguity while knowledge consists of three distinct dimensions namely education level,work experience and skills. The respondents in this study comprise of entrepreneurs in Kota Bharu, Kelantan. Hence, Pearson correlation and multiple regression analysis are conducted in order to examine the impact of personality traits and knowledge on entrepreneurs' performance. The element of personality traits based on their need for achievement, locus of control, risk-taking propensity and tolerance for ambiguity. Meanwhile for the element of knowledge consists of education level, work experience and skills. Generally, results of Pearson correlation for tolerance for ambiguity revealed that there will be no relationship between personality traits towards entrepreneur performance. Furthermore, results of multiple regression shows that that the seven (7) independent variables namely need for achievement, locus of control, tolerance for ambiguity, risk taking, education level, working experience and skills dimension were important in determining the factors influencing the entrepreneur performance in Kota Bharu, Kelantan.